Capacitively coupled hydrogen discharges : modeling vs. experiment - Marques, L. (2004)
This paper presents a systematic characterization of hydrogen capacitively coupled very high frequency discharges, produced within a parallel plate cylindrical setup, by comparing numerical simulations to experimental measurements for various plasma parameters. A good quantitative agreement is found between calculation and experiment for the coupled electrical power and the plasma potential, at various frequencies, pressures and applied voltages. However, the model generally underestimates the electron density and the self-bias potential with respect to measured values. Model predictions for the absolute density of H(n=1) atoms are compared to first diagnostic results, obtained by two-photon absorption laser-induced fluorescence diagnostics at various pressures and frequencies.